aneducation - documenta 14. - Szymczyk, Adam; Documenta Athene, Kassel 2017 (Berlin : Archive Books, 2017)
Contributors to aneducation – documenta 14: Aliaa Abou Khaddour, Sevnç Akhundova, Subhieh Alrawashdeh, Sepake Angiama, Babis Baltas, Dahlia El Broul, Clare Butcher, Barbara Ida Campaner, María Magdalena Campos-Pons, Sky (Miriam) Carranza, Raven Chacon, Weiyi Chang, Panos Charalambous, Nikhil Chopra, Ciudad Abierta (Open City), Moyra Davey, Alkisti Efthymiou, Bonita Ely, Natalia Escudero López, Aboubakar Fofana, Juliane Gallo, Maximilian Gallo, Daniel García Andújar, Anne Garthe, Gauri Gill, Aylin Gönenç, Sanchayan Ghosh, Ayşe Güleç, Irena Haiduk, Keiko Higashi, Mira Hirtz, Rangoato Hlasane, Gordon Hookey, Candice Hopkins, Necmiye Iskender, Amelie Jakubek, Mona Jas, Neslihan Kabak, Sarah Maria Kaiser, Natalie Karaitiana, Andreas Ragnar Kasapis, Anton Kats, Yul Koh, Gila Kolb, Tim König, Zvonimir Kontrec, Aynur Köşeler, Annette Kulenkampff, Katalin Ladik, Gerhard Lang, Yuyen Lin-Woywod, Ibrahim Mahama, Hans Ragnar Mathisen/Keviselie, Annika Mayer, Lala Meredith-Vula, Marta Minujín, Christa Mojab, Naeem Mohaiemen, Joar Nango, Rosalind Nashashibi, Bonaventure Soh Bejeng Ndikung, Aiko Okamoto, Nikolay Oleynikov, Georgios Pappadopoulos, Elli Paxinou, Dan Peterman, Jeannette Petrik, Nathan Pohio, Alessandra Pomarico, Pope.L, Esther Poppe, Malali Rasa, Katharina Reinhold, Erik Ritzel, Dieter Roelstraete, Clara Ronsdorf, Lala Rukh, SAVVY Contemporary, Hind Salti, Khvay Samnang, Mateusz Sapija, Konstanze Schütze, Andara Shastika, Ahlam Shibli, David Smeulders, Mounira Al Solh, Philipp Spillmann, Verena Sprich, Adam Szymczyk, Vincent Tao, Arda van Tiggelen, Maya Tounta, Leanne Turvey, Sadaf Vasaei, Cecilia Vicuña, Ayfer Vural, Cilian Woywod, Laurie White, Zafos Xagoraris, Arnisa Zeqo, Mary Zygouri
This is not a book of good intentions. It attempts to introduce a chorus of voices that speak from different positions on aneducation, the education program for Learning from Athens, documenta 14 in Athens and Kassel. Instead of objectives and overviews, target groups and outcomes, successes or failures, the program was determined by process and experience. In thinking through the body it was possible to examine how we come together and recognize knowledge not as a one-way transmission but as a form of exchange that can be circulated. Further, the aim was to listen and learn as an institution, be receptive, and acknowledge the complexities of hearing, from eavesdropping to listening to one’s inner voice. The mode of ‘being with’ guided our program and publication, both of which seek to lay bare the opaque relationships between education, exhibition making, and their publics.
Engels met vertaling in het Grieks.
boek